Performance enhancement of two-phase closed thermosyphon with threaded evaporator surface - Kang, Sukkyung; Lee, Seokjin; Lee, Jungho (International Communications in Heat and Mass Transfer, 2025)
This study investigated the performance of a two-phase closed thermosyphon (TPCT) with a threaded evaporator surface, which is more suitable for industrial application than modified surfaces considered in the literature, such as microporous coatings, wet etching, and sandblasting in terms of economics, productivity, durability, and scalability. We evaluated the thermal performance of a threaded evaporator-bare condenser combination TPCT for four different pitches and heights of threading taps, specifically for the evaporator heat transfer coefficient (HTC), condenser HTC, and TPCT thermal resistance. In the evaporator section, the threaded surface significantly enhanced film evaporation by inducing liquid spreading and also increased the heat transfer area by up to 1.89 times, resulting in a higher evaporator HTC of up to 899.2% compared to the bare surface. On the other hand, in the condenser section, the enhanced evaporator performance increased the amount of liquid condensate, resulting in a thicker liquid film and a reduction in condenser HTC up to 53.5%. The thermal resistance of threaded-bare TPCT was reduced by up to 66.3% compared to bare-bare TPCT due to significant improvements in evaporator performance, particularly at low heat fluxes. Meanwhile, there was no noticeable difference in TPCT thermal resistance depending on the pitch and height of the thread structure, suggesting that it is advisable to use a threading tap with a larger pitch and height for better machinability in industrial fields.
Keywords: Condenser heat; Heat transfer co-efficients; Microporous coatings; Modified surfaces; Performance; Performance enhancements; Surface-modification; Thermal; Threaded surface; Two-phase closed thermosyphon; Performance enhancement; Surface modification; Threaded surface; Two-phase closed thermosyphon